Tephra From the 3 March 2015 Sustained Column Related to Explosive Lava Fountain Activity at Volcán Villarrica (Chile) - Romero, Jorge E.; Vera, Franco; Polacci, Margherita; Morgavi, Daniele; Arzilli, Fabio; Alam, Mohammad Ayaz; Bustillos, Jorge E.; Guevara, Alicia; Johnson, Jeffrey B.; Palma, José L.; Burton, Mike; Cuenca, Evelyn; et al. (Frontiers in Earth Science, 2018)
Exceptionally intense lava fountains at open conduit volcanoes are infrequent, hazardous and little-warned events. Studying their tephra falls may reveal conduit dynamics, eruption source parameters and fragmentation mechanisms. Villarrica Volcano (Southern Andes of Chile) has sustained persistent open conduit activity, associated with a dynamic lava lake since at least 1984–85. Increased seismicity and degassing in August 2014 were followed by Strombolian activity starting in February 2015 and culminated with a 1.5 km-high lava fountain on 3 March 2015. This eruption produced tephra fallout, spatter agglutination, clastogenic lavas and mixed avalanche deposits. Here we characterized for first time Villarrica's 3 March 2015 tephra fall deposits produced by lava fountain and its rapid transition to sustained eruption column, providing valuable information on paroxysmal activity in open conduit volcanoes. Tephra was dispersed southeast of the crater in a narrow, elongated, nearly-elliptic area. Minimum observed tephra loading was estimated to be 80–120 g/m2 at crosswind locations, while maximum load estimation was about 11,500 g/m2, at 7–9 km distance from the vent. At 6–8 km downwind, the tephra fall deposit consisted of a single black scoria layer; fall varied from a lapilli blanket at medial distances (9–19 km) to a few individual particles at distal sites (20–43 km). All samples are vitrophyric and contain plagioclase (3–30%), clinopyroxene (2–5%), olivine (1–4%) and orthopyroxene (<1%) phenocrysts. We estimate that 1.4 × 109 kg, equivalent to 2.4 × 106 m3 of basaltic andesite tephra (52.7–54.7 SiO2 wt. %), were erupted within a period of about 16 min at a mass eruption rate of 1.5 × 106 kg/s. The sustained eruption column height was estimated at 10.8 km, with magnitude and intensity of 2.11 and 9.13 respectively. We propose that a rejuvenated, volatile-rich magmatic intrusion probably triggered paroxysmal activity. The Villarrica eruption is classified as a short-lived, large-scale lava fountain, similar to analogous historical events at Mt. Etna and Kilauea. As evident by devastating twentieth century Villarrica eruptions which also developed similar lava fountains, this eruption style should be considered as frequent and a potential source of volcanic hazard in the future.